Penerapan Model Project Based Learning (PjBL) untuk Meningkatkan Hasil Belajar Siswa Kelas X Agribisnis Tanaman Panganan Holtikultura SMKN 1 Gondang Nganjuk - Yeni Listiana Purnama Putri; Pramita Laksitarahmi Isrianto; Siti Nuriyah (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2025)
Improving the quality of leraning in vocational high school (SMK) is essential to meet the demands of a competency-based workforce, especially in the Agricultural Food Crop and Horticultural Agribusiness expertise program. One of the challenges faced is the low student achievement in practical subjects, such as Grafting techniques. This study aims to enhance the learning outcomes of grade X ATPH 2 students at SMK negeri 1 Gondang through the implementation of the Project-Based Learning (PjBL) model in the Agribusiness Food Crop and Horticulture subject, focusing on grafting material. This research employed a Classroom Action Research (CAR) method conducted in two cycles, starting from the pre-cycle to cycle I. the research involved 30 students and was conducted from February to April 2025. The instrument used was a cognitive test analyzed quantitatively to measure student learning outcomes. The results showed an increase in the average student score from 51.23 in the pre-cycle to 76.2 in cycle I. the percentage of learning mastery also significantly increased from 16% to 57%. The implementation of the Project-Based Learning (PjBl) model provided a concrete and comprehensible learning experience, enhancing student participation and motivation.